Synthesis and Structure Characterization of SiO2 from Petung Bamboo Leaf Ash (Dendrocalamus asper (Schult.f.) Backer ex Heyne) - Wirda Udaibah; Agus Priyanto (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2017)
The Research about Synthesis and Characterization of SiO2 have been worked. We have synthesized Silica from “petung”bamboo leaf ash as SiO2 source. This step used sol gel methode. SiO2 were characterized by Fourier Transform Infra Red (FTIR) to investigated the stucture andX-Ray Diffaction to know about structure and crystallinity. FTIR spectra show peak at 617,22 cm-1 area that spesific for Si-H bond, peak at 786,96 cm-1and 1095,57 cm-1 area specific for Si-O-Si bonds. Difractogram of SiO2 show that there are peak at 2θ 21,99; 31,67 and 38,88 were specific for SiO2 that calcinated at 800oC, while for SiO2 that calcinated at 400oC there were no peak at 2θ 31,67 dan 38,88. That peaks not shown may be because low crystallinity of SiO2 that calcinated at 400oC. Calcination temperature greatly affects the crystallinity of SiO2.©2017 JNSMR UIN Walisongo. All rights reserved.